Deviant women: female crime and criminology in revolutionary Russia, 1880 - 1930 - Kowalsky, Sharon A. 19XX- (Northern Illinois University Press, 2009)
Anthropology, sociology and female crime : the origins of criminology in Russia -- Professionals, social science, and the state : the organization of Soviet criminology -- The woman's sphere : the role of sexuality in female crime -- The geography of crime : city, countryside, and trends in female criminality -- A remnant of the old way of life : infanticide in theory and practice